I.R.L. - Goebel, Jenny (New York : Scholastic Press, 2025)
Not every kid would be thrilled to move to rural Alaska, but sixth grader Lucy is eager to leave her bullies behind and start over. However, it turns out that Lucy's new school does remote learning from October to April, when the roads become too icy to navigate safely. Being the new kid is hard enough--how is she going to make friends when she can't meet anyone in person? As the ice starts to thaw, Lucy grows increasingly excited about meeting her new friends in person. But when she enters the school's address on her phone's GPS, it leads her to a crumbling, clearly abandoned building with a rotted wood sign in front --a sign that reads White Pine Secondary School.
3-6
Keywords: Haunted schools -- Juvenile fiction; Country life -- Juvenile fiction; Distance education -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Alaska -- Juvenile fiction; Middle school students -- Juvenile fiction; Ghost stories; Horror fiction